Role of bone-anabolic agents in the treatment of breast cancer bone metastases - Suvannasankha, Attaya (Breast Cancer Res, 2014)
Skeletal metastases are an incurable complication afflicting the majority of patients who die from advanced breast cancer. They are most often osteolytic, characterized by net bone destruction and suppressed new bone formation. Life expectancy from first diagnosis of breast cancer bone metastases is several years, during which time skeletal-related events - including pain, fracture, hypercalcemia, and spinal cord compression - significantly degrade quality of life. The bone marrow niche can also confer hormonal and chemo-resistance. Most treatments for skeletal metastases target bone-destroying osteoclasts and are palliative. Recent results from the Breast cancer trials of Oral Everolimus-2 trial suggest that agents such as the mammalian target of rapamycin inhibitor everolimus may have efficacy against breast cancer bone metastases in part via stimulating osteoblasts as well as by inhibiting tumor growth. Selective estrogen receptor modulators similarly inhibit growth of estrogen receptor-positive breast cancers while having positive effects on the skeleton. This review discusses the future role of bone-anabolic agents for the specific treatment of osteolytic breast cancer metastases. Agents with both anti-tumor and bone-anabolic actions have been tested in the setting of multiple myeloma, a hematological malignancy that causes severe osteolytic bone loss and suppression of osteoblastic new bone formation. Stimulation of osteoblast activity inhibits multiple myeloma growth - a strategy that might decrease breast cancer burden in osteolytic bone metastases. Proteasome inhibitors (bortezomib and carfilzomib) inhibit the growth of myeloma directly and are anabolic for bone. Drugs with limited anti-tumor activity but which are anabolic for bone include intermittent parathyroid hormone and antibodies that neutralize the WNT inhibitors DKK1 and sclerostin, as well as the activin A blocker sotatercept and the osteoporosis drug strontium ranelate. Transforming growth factor-beta inhibitors have little tumor anti-proliferative activity but block breast cancer production of osteolytic factors and are also anabolic for bone. Some of these treatments are already in clinical trials. This review provides an overview of agents with bone-anabolic properties, which may have utility in the treatment of breast cancer metastatic to the skeleton. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13058-014-0484-9) contains supplementary material, which is available to authorized users.